Реализация stem-образования детей дошкольного возраста через проектно-исследовательскую деятельность - Bogdan, Tatiana; Čerevatenko, Тatiana (Student Niepełnosprawny. Szkice i Rozprawy, 2019)
This article is focused on the implementation of preschool children’s program for the development of ‘STREAM Education or Path to the Universe’. Different possibilities for educating a creative personality are revealed through the project research. In this article the authors’ program called ‘The Fixies’, a project-research activity for kids aged 4 to 5, is presented. The authors describe the experience of using this programme in the Chernihiv branch of Unikum Academy, the Institute of the Gifted Child National Academy of Pedagogical Sciences of Ukraine and in Chernihiv 42 kindergarten. The experience gained while organizing a STREAM laboratory, which provided opportunities to use the project-research activity in the kindergarten, is described in this article.